Hemostatic profile detailing in apparent VWD cases: A cross sectional study - Fatmah S. Alqahtany (Elsevier, 2021)
The von willebrand disease (vWD) accounts to be one of the most common hereditary bleeding ailment that amounts its incidence to almost 1.5% of normal population. It is mostly associated with a defect in primary hemostasis as well as secondary defect in coagulation factor VIII as diagnosis of vwd happened to be challenging with earlier diagnostic criteria’s. Testing Vwd in menorrhagia patients was not at ease. A cross-sectional study was conducted in female patients who have visited obstetrics and gynecology clinic at King Saud University Medical City (KSUMC), Riyadh, Saudi Arabia. The inclusion criteria consist of adult female patients between 16 and 45 years old with menorrhagia. A sample of 45 patients were screened and selected for the above-mentioned study. The SPSS Statistical analysis package was performed to analyze the data’s. The fisher’s exact test was conducted to compare the demographic variables. The independent samples t-test was conducted to compare the means of subjects. The P value of ≤0.05 considered as statistically significant. The cases manifested with a history of bleeding during periods stretching from 7 to 90 days. The vWD was reported in 6.6 % (n = 3) women out of the total 45 patients. The vWF: Ac mean ± SD (51.4 ± 6.3) and vWF: Ag Mean ± SD (93 ± 67) were significantly lesser in vWD patients with that of non-vWD (98.7 ± 22.6) vs (116 ± 42.4) (p = 0.027) (p = 0.032) respectively. WBC, ESR, MCV, MCH, Hemoglobin, PLT count, INR, PT, APTT and FVIII showed no significant difference among the groups (p > 0.05).